1994
DOI: 10.1111/j.1399-3054.1994.tb02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐bound glucosamine acetyltransferase in coleoptile segments of Avena sativa

Abstract: The in vivo metabolism of D‐[U‐14C]glucosamine and the in vitro properties of glucosamine acetyltransferase (EC 2.3.1.3), the first committed enzyme in the metabolism of exogenously supplied D‐glucosamine, were studied in coleoptile segments of Avena sativa L. cv. Sole II. D‐[U‐14C]glucosamine was taken up by oat coleoptile segments and sequentially metabolised to radioactive N‐acetylglucosamine, N‐acetylglucosamine 6‐P, N‐acetylglucosamine 1‐P, UDP‐N‐acetylglucosamine and UDP‐N‐acetylgalactosamine. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…GlmA shows only very weak amino acid sequence homology with characterized enzymes of the GNAT family but exhibits an overall identity of up to 36% with predicted N-acetyltransferases of various species of the Clostridium and Thermoanaerobacter genera, including the two extremely thermophilic ethanol-and acetateproducing organisms T. mathranii strain A3 and T. tengcongensis strain MB4 (14,34). GlcN N-acetyltransferase activity has been identified in crude pigeon liver extracts and membrane fractions isolated from oat coleoptile segments, which are so far the only descriptions of such an enzymatic activity (9,21). This is thus the first report of a cloned and characterized GlcN N-acetyltransferase (EC 2.3.1.3).…”
Section: Discussionmentioning
confidence: 99%
“…GlmA shows only very weak amino acid sequence homology with characterized enzymes of the GNAT family but exhibits an overall identity of up to 36% with predicted N-acetyltransferases of various species of the Clostridium and Thermoanaerobacter genera, including the two extremely thermophilic ethanol-and acetateproducing organisms T. mathranii strain A3 and T. tengcongensis strain MB4 (14,34). GlcN N-acetyltransferase activity has been identified in crude pigeon liver extracts and membrane fractions isolated from oat coleoptile segments, which are so far the only descriptions of such an enzymatic activity (9,21). This is thus the first report of a cloned and characterized GlcN N-acetyltransferase (EC 2.3.1.3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the metabolism of D-[U-14 C]glucosamine in Calluna seedlings (Piro et al 1988), in excised bean and corn root tips (Roberts 1970) and in Koliella antarctica (Lenucci et al 2006), starts with the formation of only radioactive N-acetyl-D-glucosamine. In oat coleoptiles, an enzyme acetylating D-glucosamine has been reported (Piro et al 1994). Nevertheless, enzymes phosphorylating D-glucosamine have been isolated from yeast (Brown 1951) and higher plants (Saltman 1953).…”
Section: Resultsmentioning
confidence: 98%
“…14 C]glucosamine is sequentially metabolized by K. antarctica cells into N-acetylglucosamine, N-acetylglucosamine 6-phosphate, N-acetylglucosamine 1-phosphate, UDP-N-acetylglucosamine and UDP-N-acetylgalactosamine, according to the pathway reported in land plants (Roberts, 1970;Piro et al, 1988Piro et al, , 1994.…”
Section: All Other Amino-sugars Were Present These Results Indicatedmentioning
confidence: 99%
“…Immuno-recognition with SBA and HPA was used to reveal the presence of terminal residues of N-acetylgalactosamine. (Roberts, 1970;Piro et al, 1988Piro et al, , 1994. The D-[U-14 C]glucosamine, exogenously supplied to the microalga investigated, is first acetylated to N-acetylglucosamine and then phosphorylated to N-acetylglucosamine 6-P.…”
Section: All Other Amino-sugars Were Present These Results Indicatedmentioning
confidence: 99%
See 1 more Smart Citation